2003
DOI: 10.1677/erc.0.0100111
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive hypersensitivity to estrogen: mechanism for superiority of aromatase inhibitors over selective estrogen receptor modulators for breast cancer treatment and prevention.

Abstract: Clinical observations suggest that human breast tumors can adapt to endocrine therapy by developing hypersensitivity to estradiol (E 2 ). To understand the mechanisms responsible, we examined estrogenic stimulation of cell proliferation in a model system and provided in vitro and in vivo evidence that long-term E 2 deprivation (LTED) causes 'adaptive hypersensitivity'. The enhanced responses to E 2 do not involve mechanisms acting at the level of transcription of estrogen-regulated genes. We found no evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
0
37
0
1
Order By: Relevance
“…Estrogen signaling is complex, involving two different isoforms of the estrogen receptor, ␣ (ER␣) 1 and ␤ (ER␤), as well as several different pathways that affect the expression of a number of genes either directly or indirectly. When activated by 17␤-estradiol (E2), the ERs are translocated from the cytosol to the nucleus where the nuclear ERs bind to ERE and recruit other proteins in a complex by promoting, as an activator, or blocking, as a repressor, the recruitment of RNA polymerase to the target genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen signaling is complex, involving two different isoforms of the estrogen receptor, ␣ (ER␣) 1 and ␤ (ER␤), as well as several different pathways that affect the expression of a number of genes either directly or indirectly. When activated by 17␤-estradiol (E2), the ERs are translocated from the cytosol to the nucleus where the nuclear ERs bind to ERE and recruit other proteins in a complex by promoting, as an activator, or blocking, as a repressor, the recruitment of RNA polymerase to the target genes.…”
mentioning
confidence: 99%
“…This process, which is known as the genomic pathway, is significantly involved with many diseases, including various cancers. A nongenomic pathway that involves membrane receptors and protein kinases to send the transduction signals to the nucleus has also been described (1,2). Although there have been studies involving proteomics profiling to identify estrogenresponsive proteins (3,4), the analysis of protein complexes based on a proteomics approach could provide more insights into specific signaling pathways and cross-interactions, which are rarely explored by other approaches.…”
mentioning
confidence: 99%
“…There are observations to suggest that human breast tumors can adapt to endocrine therapy by developing hypersensitivity to estradiol. Long-term estrogen deprivation of breast cells up-regulates both the MAP kinase and phosphatidyl-inositol 3-kinase pathways and during this process ERa is markedly increased [26]. There are also indications that ERß positive tumors are generally of low biological aggressiveness and are likely to respond to hormonal therapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression and its cross-talk with ERa appears to be a common feature of acquired tamoxifen-stimulated MCF-7 and T47D xenograft models (Schafer et al 2003). In parallel, Berstein et al (2003Berstein et al ( , 2004 have demonstrated that long-term tamoxifen treatment of MCF-7 breast cancer cells (LTTT) in a castrated in vivo xenograft model is associated with early adaptive increases in MAP kinase signaling. This event promotes hypersensitivity to the agonistic effects of this anti-hormone and subsequently to estradiol, where the critical role of such signaling is evidenced by marked growth inhibitory effects of a Ras antagonist.…”
Section: Dominant 'Genomic' Era/growth Factor Signaling Mechanismmentioning
confidence: 99%